Parasites of the White-Breasted Waterhen(Amaurornis phoenicurus) - Jaafar, Nurfadnida; Babjee, Shaik Mohamed Amin (2011)
of ecto- and endoparasites in one of the most common waterbird, the White-Breasted Waterhen (Amaurornis phoenicurus). Twenty-two White-Breasted waterhen were caught in the state of Selangor, Malaysia. They were of mixed ages and gender. The feathers and skin were examined thoroughly for ectoparasites and the gastrointestinal tracts, other internal organs (crop, proventriculus, kidney, heart, lungs, liver, brain and trachea), and faeces were examined for endoparasites. The Giemsa stained blood smears were examined microscopically for haemoparasites. The species of ectoparasites found in the study includes, the feather mites, Grallobia spp. detected in 100% of the birds. Other species of feather mites found, Megninia spp. were detected in 77.3% of the birds. The lice, Lipeurus spp. were found in 18.2% of the birds. Another species of lice which has yet to be identified were detected in 4.6% of the birds. Only one species of endoparasite, Capillaria spp. was found in 22.7% of the birds. One species of blood parasite was found in this study which is the Plasmodium spp., detected in 31.8% of the birds.